An approximate method for analysing non-linear systems subject to random excitation - Anh, Nguyen Dong; Hai, Ninh Quang (Vietnam Journal of Mechanics, 2000)
A solution technique based on the representation of the response of the non-linear system by a polynomial of the response of the linearized system is presented. The relation between the original non-linear system and the linearized system is introduced by considering the so-called extended moment equations and their closed set is to be solved to determine unknowns. For the Vanderpol oscillator subject to white noise excitation, the technique gives good approximation to the response moments as well as the probability density function.